(untitled) (International Journal of Engineering and Computer Science, 2017)
Multilevel converters offer advantages in terms of the output waveform quality due to the increased number of levels used in the output voltage modulation. This advantage is particularly true for cascaded Hbridge converters that can be built to produce a large number of levels thanks to their modular structure. Nevertheless, this advantage comes at the cost of multiple DC-links supplied by independent rectifiers through the use of a multi-output transformer for inverters. This frontend complicates the implementation of converters that have a high number of levels. An alternative method of using lower voltage cells with floating dc-links to compensate only for voltage distortion of an NPC converter is considered for active rectifier applications. The analogy between the floating H-bridges and series active filters is used to develop a strategy for harmonic compensation of the NPC output voltage and the control of the floating dc-link voltages. This simplifies the current control scheme and increases its bandwidth. Experimental results with a low power prototype that show the good performance of the proposed modulation technique and the resulting improvement in the output waveform are provided. Index Terms—Power elect